Interaction between positive allosteric modulators and trapping blockers of the NMDA receptor channel. (13th January 2015) - Emnett, Christine M; Eisenman, Lawrence N; Mohan, Jayaram; Taylor, Amanda A; Doherty, James J; Paul, Steven M; Zorumski, Charles F; Mennerick, Steven
<x xml:space="preserve">Abstract</x> Background and Purpose Memantine and ketamine are clinically used, open‐channel blockers of NMDA receptors exhibiting remarkable pharmacodynamic similarities despite strikingly different clinical profiles. Although NMDA channel gating constitutes an important difference between memantine and ketamine, it is unclear how positive allosteric modulators (PAMs) might affect the pharmacodynamics of these NMDA blockers. Experimental Approach We used two different PAMs: SGE‐201, an analogue of an endogenous oxysterol, 24S‐hydroxycholesterol, along with pregnenolone sulphate (PS), to test on memantine and ketamine responses in single cells (oocytes and cultured neurons) and networks (hippocampal slices), using standard electrophysiological techniques. Key Results SGE‐201 and PS had no effect on steady‐state block or voltage dependence of a channel blocker. However, both PAMs increased the actions of memantine and ketamine on phasic excitatory post‐synaptic currents, but neither revealed underlying pharmacodynamic differences. SGE‐201 accelerated the re‐equilibration of blockers during voltage jumps. SGE‐201 also unmasked differences among the blockers in neuronal networks – measured either by suppression of activity in multi‐electrode arrays or by neuroprotection against a mild excitotoxic insult. Either potentiating NMDA receptors while maintaining the basal activity level or increasing activity/depolarization without potentiating NMDA receptor function is sufficient to expose pharmacodynamic blocker differences in suppressing network function and in neuroprotection. Conclusions and Implications Positive modulation revealed no pharmacodynamic differences between NMDA receptor blockers at a constant voltage, but did expose differences during spontaneous network activity. Endogenous modulator tone of NMDA receptors in different brain regions may underlie differences in the effects of NMDA receptor blockers on behaviour.